Experimental Analysis of Out-of-Plane Structural Vibrations of Two-Wheeled Vehicles - V. Cossalter; A. Doria; R. Basso; D. Fabris (Shock and Vibration)
An analysis of the handling and stability of two-wheeled vehicles depends on structural flexibility. This paper deals with laboratory experimentation carried out to identify the vehicle's structural modes of vibration. The tests were carried out in stationary conditions considering several combinations of constraints.